Sistem Pemberian Imbalan dalam Pendidikan Islam - Gumsi, Putri Eka; Jamilus, Jamilus (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The implementation of the reward system will affect employee performance, as well as teachers. This study aims to determine the system of giving Islamic education rewards. The research method used is a literature study. Data sources in this study consist of primary data sources obtained from journals or articles and books related to the management of educators and education personnel. The data analysis used is qualitative data analysis consisting of data reduction, data presentation, and conclusions. The results of data analysis show that Islam teaches that in giving rewards in education is oriented to sincere intentions, dimensions of the world and the hereafter, the importance of morality, and the role of managers of educational institutions